2019
DOI: 10.1001/jamanetworkopen.2019.16800
|View full text |Cite
|
Sign up to set email alerts
|

Association Between e-Cigarette Use and Depression in the Behavioral Risk Factor Surveillance System, 2016-2017

Abstract: IMPORTANCE The prevalence of the use of electronic cigarettes (e-cigarettes) in the United States has grown rapidly since their introduction to the market more than a decade ago. While several studies have demonstrated an association between combustible cigarette smoking and depression, the association between e-cigarette use and depression has not been thoroughly studied. OBJECTIVE To examine the association between e-cigarette use and depression in a nationallyrepresentative sample of the adult population in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
81
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 37 publications
9
81
0
7
Order By: Relevance
“…Ever use of e-cigarettes, even once or twice, together with ever smoked even one or two puffs, were used to create the composite exposure variable to examine the association of dual use, exclusive e-cigarette use, and exclusive smoking, with the cognitive problems in youth. Ever use of e-cigarette was chosen due to previous evidence on the association of ever e-cigarette use with health conditions 28 , 29 . A longitudinal analysis using the nationally representative Population Assessment of Tobacco and Health (PATH) Waves 1, 2, and 3 adult data showed significant associations of both former e-cigarette use (including even once or twice) and current e-cigarette use at Wave 1 with incident respiratory disease at Waves 2 or 3 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ever use of e-cigarettes, even once or twice, together with ever smoked even one or two puffs, were used to create the composite exposure variable to examine the association of dual use, exclusive e-cigarette use, and exclusive smoking, with the cognitive problems in youth. Ever use of e-cigarette was chosen due to previous evidence on the association of ever e-cigarette use with health conditions 28 , 29 . A longitudinal analysis using the nationally representative Population Assessment of Tobacco and Health (PATH) Waves 1, 2, and 3 adult data showed significant associations of both former e-cigarette use (including even once or twice) and current e-cigarette use at Wave 1 with incident respiratory disease at Waves 2 or 3 29 .…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal analysis using the nationally representative Population Assessment of Tobacco and Health (PATH) Waves 1, 2, and 3 adult data showed significant associations of both former e-cigarette use (including even once or twice) and current e-cigarette use at Wave 1 with incident respiratory disease at Waves 2 or 3 29 . Another study using the combined 2016 and 2017 BRFSS survey data showed that former e-cigarette use (including even just one-time use) had a significant association with a history of clinical diagnosis of depression 28 . Thus, ever use of e-cigarettes, which includes both former use and current use of e-cigarettes, was used as the exposure variable to examine its association with the cognitive problems in youth.…”
Section: Discussionmentioning
confidence: 99%
“…E-cigarette use has also been shown to be associated with alcohol use and alcohol use disorder in nonsmokers of cigarettes [ 74 ]. Associations with asthma [ 18 ] and depression [ 13 ] have also been reported for sole e-cigarette use. Thus, our ML approach agrees with the literature confirming some known factors associated with sole e-cigarette use.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term effects of e-cigarette use remain largely unknown, but e-cigarette aerosols contain toxins that can affect health [ 5 , 6 , 7 , 8 ]. There is increasing evidence that e-cigarettes may be associated with an increased risk of oral diseases [ 9 , 10 ], prediabetes [ 11 ], depression [ 12 , 13 ], asthma, chronic obstructive pulmonary disease (COPD) and respiratory symptoms [ 14 , 15 , 16 , 17 , 18 ]. Recently, the Centers for Disease Control and Prevention (CDC) reported multiple cases of e-cigarette or vaping product use-associated lung injury (EVALI), some of which resulted in deaths [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…42 deaths have been confirmed in 24 states and the District of Columbia: Alabama, California (4), Connecticut, Delaware, the District of Columbia, Florida, Georgia (3), Illinois (4), Indiana (4), Kansas (2), Massachusetts (2), Michigan, Minnesota (3), Mississippi, Missouri, Montana, Nebraska, New Jersey, New York, Oregon (2), Pennsylvania, Tennessee (2), Texas, Utah, and Virginia" [21]. Vaping, may also have harmful psychological effects with a strong association between vaping, major depression and suicidal behavior as reported in a large new study [22]. The likely contributing culprit, nicotine.…”
Section: Reviewmentioning
confidence: 99%